Распространение и систематический статус тонкоклювой камышовки (Lusciniola melanopogon T e m m.) в Европейской части СССР - Казаков, Б.А. (Вестник зоологии, 1974)
On the basis of processing the collection materials from the Zoological Institute of the Academy of Sciences of the USSR, Zoological Museum of Moscow State University and the author's own collections, moustached warbler inhabiting the Azov Sea and the Lower Don areas is distinguished as a new subspecies —Lusciniola melanopogon, albiventris subsp. n. The new subspecies differed from the nominal (L. m. melanopogon) and the eastern (L. m. mimica) subspecies in colour and length of the metatarsal bone. Distribution of this species in the Forecaucasia and Lower Don area is specified in the article. Individuation of this subspecies in the Azov Sea area is supposed to result, from isolation of some part of the area of distribution in the period of the Pleistocene fall in temperature.